Application of iLearning Education in Learning Methods for Entrepreneurship and Elementary School Student Innovation - Rii, Kim Beom; Choi, Lee Kyung; Shino, Yamato; Kenta, Hiroshi; Adianita, Irsa Rizkita (Aptisi Transactions On Technopreneurship (ATT), 2020)
Primary school is an early age in the introduction of information and communication technology, therefore it is necessary to be prepared abilities and skills in the use of technology. Learning about entrepreneurship at the elementary school level is generally still traditional, where valuable renewal results are created. However, in this 4.0 era, many elementary students still traditionally run entrepreneurship, this has not been a challenge in line with the Ministry of Education and Culture on an independent campus. In order to create the involvement of young people in the field of entrepreneurship, the right solution is how entrepreneurship learning in Learning can be applied from an early age, namely to elementary school students. SEP (School Enrichment Program) is an entrepreneurial learning application based on iLearning aimed at elementary school students to have a high quality of creativity and a willingness to innovate at an early age. Based on the observational test results the Ubiquitous Learning Method is significantly able to influence the motivation of elementary school students to be enthusiastic in terms of entrepreneurial learning from an early age, and to show the results that Cronbach's Alpha 0.9> 0.6 ie the SEP is very accurate in its application especially can improve the results significant in influencing the formation of intentions in entrepreneurship even more starting to spread the trend of entrepreneurship which has now touched various circles, one of them among students.